Synthesis and structural characterization of some adducts of 1,4-dithian and -oxathian with silver(I) nitrate and perchlorate - Effendy; Silong, Sidik; Skelton, Brian W.; White, Allan H. (CSIRO Publishing, 2003)
The crystallographic structures of 1,4-oxathian (O(CH2CH2)2S) and its 1:1 silver(I) nitrate adduct were redetermined The 1:1 and 1.5:1 adducts of 1,4-dithian (S(CH2CH2)2S) with silver(I) nitrate and perchlorate, respectively, were also determined. The nitrate complexes formed two-dimensional polymers while the perchlorate formed a three-dimensional polymer (see Figure). The Ag coordination environments were unique in each complex formed.